Safety evaluation of a mixture of the human-identical milk oligosaccharides 2′-fucosyllactose and difucosyllactose. (October 2018) - Phipps, Kirt R.; Baldwin, Nigel; Lynch, Barry; Flaxmer, Jessica; Šoltésová, Alica; Gilby, Ben; Mikš, Marta H.; Röhrig, Christoph H.
Abstract: Human milk oligosaccharides (HMOs) are endogenous indigestible carbohydrates representing the largest compositional difference between human breastmilk and infant formula (IF). Two major HMOs in human breastmilk are 2′-fucosyllactose (2′-FL) and difucosyllactose (DFL); commercial IF can be supplemented with manufactured structurally identical versions of HMOs [known as human-identical milk oligosaccharides (HiMOs)] to better replicate the composition of human milk. As 2′-FL and DFL are always found together in human milk, a mixture of these HiMOs (2′-FL/DFL) has been proposed for use in IF and as a food ingredient. Safety assessment of 2′-FL/DFL included conduct of in vitro genotoxicity tests and a subchronic oral toxicity study. In the subchronic study, 2′-FL/DFL (8:1 ratio) was administered to neonatal rats at doses up to 5000 mg/kg body weight (bw)/day, once daily for 90 days, followed by a 4-week recovery period. A concurrent reference control group received 5000 mg/kg bw/day of an oligosaccharide already used in IF (fructooligosaccharide), for direct comparison with the high-dose 2′-FL/DFL group. No evidence of genotoxicity was observed. In the absence of compound-related adverse effects in the 90-day study, 5000 mg/kg bw/day was established as the no-observed-adverse-effect-level. These results support the use of 2′-FL/DFL in IF and as a food ingredient. Highlights: Human milk oligosaccharides 2′-fucosyllactose (2′-FL) and difucosyllactose (DFL) are always found together in human milk. Potential genotoxicity and subchronic toxicity of a mixture of manufactured 2′-FL and DFL (2′-FL/DFL) was assessed. 2′-FL/DFL was non-genotoxic in a series of in vitro tests. No treatment-related adverse effects were seen at doses up to 5000 mg/kg body weight/day in a 90-day study in neonatal rats. These results support the safe use of 2′-FL/DFL in infant formula and as a food ingredient.